2022
DOI: 10.3390/bioengineering9110683
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Electrocardiogram Classification with Multiple Datasets and Distant Transfer Learning

Abstract: Electrocardiogram classification is crucial for various applications such as the medical diagnosis of cardiovascular diseases, the level of heart damage, and stress. One of the typical challenges of electrocardiogram classification problems is the small size of the datasets, which may lead to limitation in the performance of the classification models, particularly for models based on deep-learning algorithms. Transfer learning has demonstrated effectiveness in transferring knowledge from a source model with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The transformer networks have efficiency advantages, capturing long-range dependencies, extracting global information, flexibility in adjustment, and good generalization ability. Therefore, transformer networks have been widely used in various tasks, such as natural language processing, machine translation, sentiment analysis, and image processing [ 11 , 19 , 20 , 21 , 22 ]. Natarajan et al [ 11 ], Li et al [ 19 ], and Qiu et al [ 20 ] have designed transformer network architectures for ECG-based applications, and the experimental results showed that the transformer network has high performance and is valid for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The transformer networks have efficiency advantages, capturing long-range dependencies, extracting global information, flexibility in adjustment, and good generalization ability. Therefore, transformer networks have been widely used in various tasks, such as natural language processing, machine translation, sentiment analysis, and image processing [ 11 , 19 , 20 , 21 , 22 ]. Natarajan et al [ 11 ], Li et al [ 19 ], and Qiu et al [ 20 ] have designed transformer network architectures for ECG-based applications, and the experimental results showed that the transformer network has high performance and is valid for practical applications.…”
Section: Introductionmentioning
confidence: 99%